Pemberdayaan Air Tanjung oleh Masyarakat sebagai Keunikan Lokal Desa Tanjung Kecamatan Kawalu, Tasikmalaya - Dini Islami Noor; Siti Fitria Febriani; Nisha Nurul Oktaviani; Wanda Agustin; Holipah Holipah; Diana Hernawati; Lia Badriah (Poltekkes Kemenkes Yogyakarta, 2020)
Tanjung water, which can only be found in Kelurahan Tanjung of Kecamatan Kawalu, Tasikma-laya Regency, is believed by generations has uniqueness, that can make several foods more delicious. According to some sources the water contains arsenic and several other chemical components that are different from ordinary water. This study was aimed to determine the extent of empowerment by people towards Tanjung Water, by conducting a qualitative study. The data were collected by observation and interview techniques. The study results indicate that there is lack of participation from the city government in terms of funds and supervision, so that gives major impact to the condition and utilization of Tanjung Water as one of local uniqueness.